The Role Of Nanotechnology In Improving Drug Delivery For Lung Cancer (Journal of Academic Research, 2025)
Lung cancer remains one of the deadliest cancers globally, highlighting the urgent need for effective treatment strategies, the aim in this research the potential of nanotechnology in revolutionizing lung cancer treatment, focusing on inhalation chemotherapy and targeted drug delivery systems. The research begins by outlining the characteristics and challenges of lung cancer, emphasizing the importance of early detection and personalized treatment approaches. It then delves into the application of nanotechnology in medicine, specifically highlighting the advantages of nanocarriers for drug delivery, thJanuary and June 2024, The number of male cases was 571, while female cases numbered 515. It is worth noting that there were 95 cases of lung cancer, 80 of which were among males and 15 among females, the most affected age group was those over the age of sixty, Data obtained from the institute indicated that the stage of disease detection for the majority of patients was either unrecorded or possibly unknown. It was also noted that the diagnosis of these cases was not accurate in determining whether the cancer was of the NACLC or SCLC type, The research also explores the development of inhalable formulations for lung cancer treatment, emphasizing the advantages of direct and non-invasive drug delivery to the lungs, leading to improved bioavailability and therapeutic index. The research concludes by highlighting the immense potential of nanotechnology in improving lung cancer treatment outcomes, emphasizing the need for continued research and development of sophisticated nanocarriers capable of effectively targeting and treating lung cancer